Unusual Manifestations of Dengue Fever: A Review on Expanded Dengue Syndrome - Umakanth, Maheswaran (Cureus, 2020)
Dengue infection may manifest as dengue fever (DF), dengue hemorrhagic fever (DHF), and dengue shock syndrome (DSS). The World Health Organization (WHO) came up with the term "expanded dengue syndrome" (EDS) to designate cases which do not fall into either DHF or DSS, with unusual manifestations in other organs such as the cardiovascular system, the nervous system, the kidneys, the gut, and the hematological system, which have been increasingly reported and called EDS. Furthermore, EDS is becoming widespread globally with unusual features and increased severity. There are increasing reports of under-recognized and infrequent manifestations with severe organ involvement. This review gives knowledge of expanded dengue syndrome which helps to catch the diagnosis of dengue early, particularly during the ongoing epidemics and escaping from further series of unnecessary investigations.